Factors influencing success / failure of reference interviews - Villalonga, Graciela T. (Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study was conducted to examine the factors affecting reference interview. specifically, it aimed to find out 1) the initial response and behavior of the library staff when asked reference questions and its impact on the questionnaire; 2) the strategy library staff used to respond to reference queries; 3) the predominant model of reference practice used by the library staff; 4) whether a follow-up question was used or not; and 5) the factors that contribute to the success or failure of the reference interview.